Characteristics of macroreentrant atrial tachycardias using an anatomical bypass: Pseudo‐focal atrial tachycardia case series. (8th August 2021) - Nakatani, Yosuke; Nakashima, Takashi; Duchateau, Josselin; Vlachos, Konstantinos; Krisai, Philipp; Takagi, Takamitsu; Kamakura, Tsukasa; André, Clémentine; Goujeau, Cyril; Daniel Ramirez, F.; Chauvel, Remi; Tixier, Romain; et al.
Abstract: Introduction: Human atria comprise distinct layers. One layer can bypass another, and lead to a downstream centrifugal propagation at their interface. We sought to characterize anatomical substrates, electrophysiological properties, and ablation outcomes of "pseudo‐focal" atrial tachycardias (ATs), defined as macroreentrant ATs mimicking focal ATs. Methods and Results: We retrospectively analyzed left atrial ATs showing centrifugal propagation with postpacing intervals (PPIs) after entrainment pacing suggestive of a macroreentrant mechanism. A total of 22 patients had pseudo‐focal ATs consisting of 15 perimitral and 7 roof‐dependent flutters. A low‐voltage area was consistently found at the collision site and colocalized with distinct anatomical structures like the: (1) coronary sinus‐great cardiac vein bundle (27%), (2) vein of Marshall bundle (18%), (3) Bachmann bundle (27%), (4) septopulmonary bundle (18%), and (5) fossa ovalis (9%). The mean missing tachycardia cycle length (TCL) was 65 ± 31 ms (22%) on the endocardial activation map. PPI was 0 [0–15] ms and 0 [0–21] ms longer than TCL at the breakthrough site and the opposite site, respectively. While feasible in 21 pseudo‐focal ATs (95%), termination was better achieved by blocking the anatomical isthmus than ablating the breakthrough site [20/21 (95%) vs. 1/5 (20%); p < .001]. Conclusion: Perimitral and roof‐dependent flutters with centrifugal propagation are favored by a low‐voltage area located at well‐identified anatomical structures. Comprehensive entrainment pacing maneuvers are crucial to distinguish pseudo‐focal ATs from true focal ATs. Blocking the anatomical isthmus is a better therapeutic option than ablating the breakthrough site.